Hubungan Antara Pertumbuhan Ekonomi dan Infrastruktur Transportasi di Indonesia - Sukesa, Ida Kade; Papyrakis, Elissaios (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
Given the mixed results of the existing research on the relationship between transport infrastructure and economic growth in Indonesia, this study, which aims to examine this relationship, uses two approaches, first using time-series data and second using panel data. From the first approach, this study concludes that there is a unidirectional relationship from economic growth to road infrastructure, while between economic growth and air and sea transportation infrastructure there is no relationship. Similar results were also found using the second approach. The growth of three types transport infrastructure does not have a significant effect on economic growth.